Data classification – the foundation of information security. Issue 5 (May 2015) - Tankard, Colin
Abstract : Data is the lifeblood of any organisation and has enormous value. Such data includes intellectual property and trade secrets, financial and customer records, and information related to employees. Much of that data is sensitive, and it is also of enormous value to those who would like to steal it for financial gain or commercial advantage. Data classification is a foundational technology for ensuring effective data security and information governance by applying protective markings to documents. Combined with clear policies and processes, this bolsters the capabilities of other controls used by organisations to safeguard data, such as data loss prevention and encryption technologies, helping to improve the overall security posture and to protect an organisation. It's key to your organisation's security, says Colin Tankard of DigitalPathways.